Islamic Corporate Governance, Islamic Social Reporting, Financial Performance and Tax Avoidance: Women BOD and Leverage as Moderating Variables (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2023)
The impact of Islamic Corporate Governance (ICG), Islamic Social Reporting (ISR), and financial performance on tax avoidance is investigated in this study. Islamic Corporate Governance is represented by the Sharia Supervisory Board (DPS), institutional ownership, the audit committee, and independent commissioners (ICG). The effective tax rate is used to measure tax avoidance, while ROA is used to measure financial performance (ETR). Twelve Indonesian Sharia Commercial Banks that were registered with OJK between 2016 and 2021 make up the study's sample. Panel data regression is the data analysis method used. MRA analysis is additionally utilized to observe the impact of moderating variables. The study's findings indicate that tax avoidance is unaffected by DPS, institutional ownership, the audit committee, and the percentage of independent commissioners. Tax avoidance is negatively impacted by Islamic Social Reporting (ISR) and ROA. The moderating variable in this study cannot moderate the association between the audit committee and tax avoidance, specifically the women's Board of Directors (BOD). The relationship between Islamic corporate governance (ICG) and tax compliance also cannot be moderated by leverage. This research is anticipated to be taken into account by the government when drafting tax legislation to reduce tax avoidance strategies used by businesses, particularly Islamic banks. In addition, it is hoped that it will become a consideration for both financial institutions and companies to improve ISR performance and reporting as a social responsibility so that tax avoidance practices can be minimized.